Y- chromosomal STR Variation in Arab, Soran and Behdinan Kurds population in Kurdistan region of Iraq - Ehsaan, Heja Saadallah; Fattah, Yousif Mohammed (Technium BioChemMed, 2022)
Background: Over than eight tenant groups make up Kurdistan region of Iraq local populations. Overall majority of the inhabitants are Muslim Kurds, followed by Yezidi Kurds. Alternative groups including Armenians, Assyrian, Chaldea Syriacs as well as a little minority of Arab and Turkmen individuals. Methods: A total of 60 unrelated males from three population groups in Kurdistan region of Iraq Arabs, Soran and Behdinan kurd were successfully analyzed for ten Y- chromosome STRs (DYS19, DYS390, DYS393, DYS437, DYS439, DYS447, DYS460, DYS461, DYS481, DYS576). Whole DNA has been extracted from the blood samples using DNA extraction kit. PCR products were run on 8% polyacrylamide gel with a 50bp DNA ladder marker to size the bands for each sample. silver staining was used to identify the DNA bands. Power Marker V3.25 software was used successfully to determine a variety of genetic parameters which include total allele number, allele frequency, gene diversity and polymorphic information content (PIC). Phylogenetic tree was constructed by MEGA-X software. Results: The total number of alleles identified in the three populations was 155. The size of the alleles ranged from 112bp to 245bp. The DYS19 had the highest diversity (GD: 0.941), whereas DYS393 locus had the lowest value among all (GD: 0.813). The Dendrogram split the populations into two main clusters: Arabs in one cluster, whereas Soran and Behdinan in another cluster. Conclusions: This study validates that the discrimination potential of high-resolution Y-STR typing and supports the main datasets on the samples from Kurdistan region of Iraq. The comparison of two group of Kurds and Arab datasets offers an intriguing total pattern of Kurd groups. Meaning that Sorans are genetically closer to the Behdinan population.